Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Melalui Komitmen Kerja sebagai Variabel Intervening pada RS Sakinah Mojokerto - Eka Rizky Raditya Widiono; Kasnowo Kasnowo; Rini Armin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Workload and work stress are important human resource issues in hospitals because both are closely related to employee performance and service quality. This study aims to analyze the direct effects of workload and work stress on employee performance and the indirect effects through work commitment as an intervening variable at Sakinah Hospital Mojokerto. The study used a quantitative causal approach and a survey method. The population consisted of 150 nurses and the sample was 109 respondents selected using simple random sampling with the Slovin formula at a 5% error tolerance. Data were collected using a Likert-scale questionnaire and analyzed with validity and reliability tests, classical assumption tests, multiple linear regression, path analysis, coefficient of determination, t-tests, and Sobel tests. The results show that workload has a positive and significant effect on employee performance, while work stress has a negative and significant effect. Work commitment has a positive and significant effect on performance and significantly mediates the effects of both workload and work stress on performance. The findings indicate that workload that remains manageable can support performance, whereas excessive work stress can reduce performance; maintaining work commitment can strengthen positive effects and buffer negative effects.